Education, Training and Labor Market Outcomes for Youth in Indonesia - World Bank (World Bank, 2012)
This report is part of the Analytical and Advisory Activities (AAA) program focusing on the engagement area of 'skills development, competitiveness, and knowledge economy' and is based on several background papers and technical notes written on the characteristics of youth employment and the role of education and skills in the school-to-work transition in Indonesia. The slow transition of graduates is explored in detail in section two, which pays special attention to differences by education levels. It highlights the difficulties of senior secondary school graduates in accessing good quality jobs and the high unemployment rate that they face upon graduation. Given these worrisome signs of young senior secondary school graduates (considered the lower tier of 'skilled' workers) and expected increases in the transition to senior secondary education (which are already rising rapidly), section three focuses on the senior secondary school level. Seeking to shed some light on the question of whether senior secondary education is providing the right skills for its students, the section explores the employment profile of vocational (SMK) vs. general (SMA) graduates and, drawing on a recent survey of employers, argues against a drastic increase in the proportion of vocational students, highlighting instead the need to adjust the skill base of senior secondary school graduates. Based on the findings, section four explores ways to meet the demand for skills through changes in senior secondary school, strengthening of the non-formal training system and providing targeted entrepreneurship programs. Finally, section five provides some overall recommendations going forward.